Analisis Kurikulum Sekolah Dasar di Korea Selatan - Aulia Azzahra; Sri Marmoah (STKIP Subang, 2026)
The curriculum is a plan that includes objectives, content, methods, and assessment. The curriculum in South Korea is designed systematically and oriented towards global needs, especially at the elementary school level, which emphasizes mastery of science, technology, and the development of creativity and 21st-century skills. This study aims to analyze the South Korean curriculum, especially in elementary schools, starting from its implementation, curriculum development factors, as well as its strengths and weaknesses. This study uses a literature review approach from 26 articles, including national and international articles, as well as articles from online portals. The results show that, overall, the South Korean education system has succeeded in creating a learning environment that is disciplined, innovative, and globally oriented. However, the main challenges that need to be addressed are reducing excessive academic pressure, expanding regional educational autonomy, and ensuring a balance between academic achievement and the emotional well-being of students. Therefore, there is a need for continuous evaluation by the government of the current curriculum and improvement of existing problems.